Ernst Tugendhat, Donald Winnicott e Margaret Mahler: os cuidados ao bebê e saúde mental - Louzada Neto, Antônio Peyrouton (Universidade do Vale do Rio dos Sinos, 2017)
This Study aims to correlate the work of the German philosopher Ernst Tugendhat with the works of the English psychoanalyst Donald Winnicott and the Hungarian psychoanalyst Margaret Mahler, regarding the importance of the early relationship between mother and child, as well as its effects on the child’s mental health and its later adult life. From Mahler’s work, the phases of child development were used in this study, in regards to the psychological birth of the child. From Winnicott’s work, four main ideas were selected, regarding the importance of maternal care in child development. From Tugendhat’s work, the book Egocentricity and Mysticism: An Anthropological Study was used for this analysis, specially the chapter in which the author analyses the importance of the early relationship between mother and child in later life mental health. Each author’s main ideas are described separately. Afterwards, there is a comparison of Tugendhat’s work with the psychoanalytical theory of Winnicott and Mahler. In the end, there is a clinical case which exemplifies the concepts presented in the study.
Keywords: Ernst Tugendhat; Donald Winiccott; Margareth Mahler; Relação mãe-bebê; Mãe suficientemente boa; Cuidados maternos; Nascimento psicológico da criança; Cuidados ao bebê; Mother-child relationship; Good-enough mother; Maternal care; Psychological birth; Childcare